Modelling the cost of ewe mortality in New Zealand sheep flocks - Ridler AL; Corner-Thomas RA; Tozer P (Elsevier B.V., 2026)
CONTEXT Reported ewe mortality rates in extensively farmed sheep flocks range from 2.9–12.8%. Most deaths occur over the lambing period, and many are potentially preventable or treatable. An understanding of the costs of ewe mortality would allow farmers to determine which interventions are most cost-effective. OBJECTIVE Use a dynamic bioeconomic model to investigate the impacts of ewe mortality on cash operating surplus for New Zealand sheep flocks. METHODS An existing dataset of 23 flocks was used which comprised data on ewe numbers throughout the year, ewe deaths, reproductive data and farm demographic data (location, size, topography and stock numbers). Each flock was modelled using economic data for the 2023 financial year. Cash operating surplus per ewe (COS/ewe) was generated for each flock using their actual death rates. For flocks with death rates >4%, the effects on COS/ewe were also modelled based on a reduction in ewe deaths by 20% or 50%. RESULTS AND CONCLUSIONS Flocks with higher ewe death rates had lower COS/ewe, with an overall correlation of 0.58. Reducing deaths by 20% and 50% resulted in an increased COS/ewe of NZ$1.12 to $2.66/ewe and NZ$2.89 to $6.67/ewe, respectively. Multiplying these numbers by the total number of ewes in their flock provides guidance to producers on how much they could spend to reduce the death rate of their ewes. SIGNIFICANCE Producers can use the results, along with their flock-specific ewe mortality data, to determine cost-effective strategies to reduce ewe mortality.
Keywords: Sheep farming; Ewe mortality; Bio-economic modelling; Wastage; Animal health economics; Pasture-based systems